Time to treat the climate and nature crisis as one indivisible global health emergency - Kamran Abbasi; Parveen Ali; Virginia Barbour; Thomas Benfield; Kirsten Bibbins; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Robert Mash; Peush Sahni; Wadeia M. Sharief; Paul Yonga; et al. (AOSIS, 2023)
No abstract available.